Natural variation in the promoter of rice calcineurin B‐like protein10 (OsCBL10) affects flooding tolerance during seed germination among rice subspecies. (1st April 2018) - Ye, Neng‐Hui; Wang, Feng‐Zhu; Shi, Lu; Chen, Mo‐Xian; Cao, Yun‐Ying; Zhu, Fu‐Yuan; Wu, Yi‐Zhen; Xie, Li‐Juan; Liu, Tie‐Yuan; Su, Ze‐Zhuo; Xiao, Shi; Zhang, Hao; et al.
Summary: Rice ( Oryza sativa L.) has two ecotypes, upland and lowland rice, that have been observed to show different tolerance levels under flooding stress. In this study, two rice cultivars, upland (Up221, flooding‐intolerant) and lowland (Low88, flooding‐tolerant), were initially used to study their molecular mechanisms in response to flooding germination. We observed that variations in the OsCBL10 promoter sequences in these two cultivars might contribute to this divergence in flooding tolerance. Further analysis using another eight rice cultivars revealed that the OsCBL10 promoter could be classified as either a flooding‐tolerant type (T‐type) or a flooding‐intolerant type (I‐type). The OsCBL10 T‐type promoter only existed in japonica lowland cultivars, whereas the OsCBL10 I‐type promoter existed in japonica upland, indica upland and indica lowland cultivars. Flooding‐tolerant rice cultivars containing the OsCBL10 T‐type promoter have shown lower Ca 2+ flow and higher α‐amylase activities in comparison to those in flooding‐intolerant cultivars. Furthermore, the OsCBL10 overexpression lines were sensitive to both flooding and hypoxic treatments during rice germination with enhanced Ca 2+ flow in comparison to wild‐type. Subsequent findings also indicate that OsCBL10 may affect OsCIPK15 protein abundance and its downstream pathways. In summary, our results suggest that the adaptation to flooding stress during rice germination is associated with two different OsCBL10 promoters, which in turn affect OsCBL10 expression in different cultivars and negatively affect OsCIPK15 protein accumulation and its downstream cascade. Significance Statement: This study identifies that OsCBL10 is able to communicate with upstream calcium signaling and downstream flooding responses by affecting OsCIPK15 protein accumulation or stability. The variation in OsCBL10 promoter regions could be a general mechanism in Sub1A‐deficient lowland japonica cultivars in response to flooding germination.